A New Birthweight Reference by Gestational Age: A Population Study Based on the Generalized Additive Model for Location, Scale, and Shape Method - Wu, Qiong; Zhang, Hui-Yun; Zhang, Li; Xu, Yue-Qin; Sun, Jin; Gao, Nan-Nan; Qiao, Xiu-Yun; Li, Yan (Frontiers in Pediatrics, 2022)
Background: It is important to choose a suitable reference to assess newborns especially for small for gestational age infant (SGA). There is no regional standard for the north of China or for Shandong province. Methods: There were 130911 data records of singleton live neonatal at 24 to 42 weeks of gestation were collected between 2016 and 2018 in Shandong province. A new birth weight–for–gestational age percentile reference was constructed based the GAMLSS package in R version 3.5. The established gestational age weight curve was compared separately with Fenton curve, INTERGROWTH–21st curve and the Chinese Neonatal Network Standard curve of 2015. Results: We established the reference values of birth weight by gestational age at 3rd , 10th, 25th, 50th, 75th, 90th and 97th percentiles. Newborns in present study have much heavier birth weight than those in INTERGROWTH–21st and Fenton curve at most gestational age. Although in present study, newborns’ birth weight references are more close to Chinese Neonatal Network Standard except partially gestational age, present study and INTERGROWTH–21st have similar birth weight curve shapes. Conclusions: There are obvious differences among the criteria for newborns birth weights. It will be more accurate to assess newborns using the local birth weight reference.